White matter tract signatures of fiber density and morphology in ADHD. (May 2021) - Fuelscher, Ian; Hyde, Christian; Anderson, Vicki; Silk, Timothy J.
Abstract: Previous studies investigating white matter organization in attention deficit hyperactivity disorder (ADHD) have adopted diffusion tensor imaging (DTI). However, attempts to derive pathophysiological models from this research have had limited success, possibly reflecting limitations of the DTI method. This study investigated the organization of white matter tracts in ADHD using fixel based analysis (FBA), a fiber specific analysis framework that is well placed to provide novel insights into the pathophysiology of ADHD. High angular diffusion weighted imaging and clinical data were collected in a large paediatric cohort (N = 144; 76 with ADHD; age range 9–11 years). White matter tractography and FBA were performed across 14 white matter tracts. Permutation based inference testing (using FBA derived measures of fiber density and morphology) assessed differences in white matter tract profiles between children with and without ADHD. Analysis further examined the association between white matter properties and ADHD symptom severity. Relative to controls, children with ADHD showed reduced white matter connectivity along association and projection pathways considered critical to behavioral control and motor function. Increased ADHD symptom severity was associated with reduced white matter organization in fronto-pontine fibers projecting to and from the supplementary motor area. Providing novel insight into the neurobiological foundations of ADHD, this is the first research to uncover fiber specific white matter alterations across a comprehensive set of white matter tracts in ADHD using FBA. Findings inform pathophysiological models of ADHD and hold great promise for the consistent identification and systematic replication of brain differences in this disorder.